Feast as a Holiday and as a Conspiracy - Arakelyan, Ara (Bulletin of Yerevan University B: Philology, 2023)
The article comments on issues related to the semantics of food that are seen in mythology, folklore, and history. First, the fact that food is a biological condition of human life is emphasized, but along with history, it gradually acquires a social and spiritual meaning, directly serving as a basis for the creation of a ritual chain stretching from sacrifice to communion. Although the man, homo sapiens, is radically different from animals, the process of eating puts them closer together. In that respect, gods are no different from humans either. Special attention is paid to sacrifice, which since ancient times has served to establish and strengthen the bond between gods and humans. Along with the spiritual, ritual meal, the secular meal - the feast, is also considered. It is interpreted in two ways: as a celebration and as a conspiracy. If the connection with a god or gods (vertical connection) is especially important in ritual meals, the secular feast is mainly emphasized by strengthening the connection between the participants (horizontal connection), because eating together contains enormous moral and social power. It is not by chance that E. Canetti sees elements of power in the function of food or eating. In this regard, the main focus is on the party as a conspiracy. There are considered many examples from mythology, epic and history.